DEVELOPMENT OF EDUCATION TOURISM IN SOUTH TANGERANG REGION (CASE STUDY: KANDANK JURANK DOANK) - Asep Parantika; Abu Bakar Isnaen (Journal of Business on Hospitality and Tourism, 2016)
Education tourism is a program where tourists visit a tourism destination with the main purpose to receive experience in education directly in the tourism object. In those places visitors could do tourism activities and also studying with fun methods. Kandank Jurank Doank is a tourism object that is located in Ciputat – South Tangerang. This tourism object which applies the concept of Education Tourism has become a choice for people of Jakarta city and around for recreation because of its location which is not far from the center of Jakarta city. This research is a descriptive with the support of qualitative data. The technique of data collecting is done through observation, questionnaire interviews, and documentation study. The informants in this research are the management parties of the tourism object Kandank Jurank Doank, in order to gain data which is actual with internal and external condition in Kandank Jurank Doank. Factor Analysis Internal and External is set by the management party of Kandank Jurank Doank through questionnaire technique, and then continued by relative weight calculation of Internal and External Factors with weighing questionnaire for Internal and External Factors. After finding the relative weight of Internal and External Factors, continuing with EFE Matrix and IFE Matrix to determine the total score of EFE and IFE which later will be used to scale the I-E Matrix, and then continued with the SWOT Matrix to determine the strategies of development for the tourism object of Kandank Jurank Doank. And the strategy that is received from the SWOT Matrix is to develop the potencies that are possessed by the company and to keep the existing tourism concept, and also to optimize the management information system in the activities of education tourism in Kandank Jurank Doank, improving service and the quality of Human Resource, in the aspect of comfort and security in order to increase the satisfaction of the consumers, designing education tourism activites that utilize the existing space and facilities, improving the cooperation with government, local people, and also the tourists themselves, and to utilize the use of internet to maximise the promotion program and the information of the tourism object of Kandank Jurank Doank, and also to form cooperations with investors in order to help the development of Kandank Jurank Doank.